Nivel de conocimiento sobre el diagnóstico y tratamiento de la hipomineralización molar incisivo (HMI) según nivel de estudio en estudiantes de odontología, UNAP-2025 - García Pérez, Carla Kassandra (2025)
Molar incisor hypomineralization (MIH) is a qualitative enamel defect affecting permanent first molars and incisors, causing sensitivity, fractures, and restorative difficulties. The aim of this study was to determine the level of knowledge about the diagnosis and treatment of MIH according to the academic level of dental students at the National University of the Peruvian Amazon (UNAP), 2025. This was a non-experimental, descriptive, and comparative cross-sectional study. The population consisted of 106 students from the fifth and sixth academic levels, who completed a validated questionnaire assessing etiology, diagnosis, and therapeutic management. Results showed that 75.4% of students had poor knowledge, 20.8% fair, and only 3.8% good. Regarding diagnosis, 67.9% showed poor knowledge and 83% lacked therapeutic understanding. A significant difference was found between academic level and knowledge (χ² = 11.232; p = 0.004), with sixth level students performing better. It is concluded that the overall knowledge of MIH among UNAP dental students is low, highlighting the need to strengthen curricular content and clinical training on enamel defects.